Coupled application of R and WetSpa models for assessment of climate change impact on streamflow of Werie Catchment, Tigray, Ethiopia - Selam Kidanemariam (IWA Publishing, 2021)
This research assesses the streamflow response of Werie River to climate change. Baseline (1980–2009) climate data of precipitation, maximum and minimum temperature were analyzed using delta based statistical downscaling approach in R software packages to predict future 90-year (2010–2099) periods under two emission scenarios of Representative Concentration Pathways (RCP) 4.5 and RCP 8.5, indicating medium and extremely high emission scenarios respectively. Generated future climate variables indicate Werie will experience a significant increase in precipitation, and maximum and minimum air temperature for both RCPs. Further, Water and Energy Transfer between Soil, Plants, and Atmosphere (WetSpa) was applied to assess the water balance of Werie River. The WetSpa model reproduced the streamflow well with performance statistics values of R2 = 0.84 and 0.85, Nash–Sutcliffe efficiency = 0.72 and 0.72, and model bias = –0.14 and –0.15 for the calibration data set of 1999–2010 and validation data of 2011–2014, respectively. Finally, by taking the downscaled future climate variables as input, WetSpa future prediction shows that there will be an increase in the Werie catchment mean annual streamflow up to 29.6% for RCP 4.5 and 35.6% for RCP 8.5 compared to the baseline period. HIGHLIGHTS In this study integrating AgMIP climate downscaling script in R-program with hydrological WetSpa model for prediction of catchment wide streamflow response to climate change have been proven to give acceptable results.; Future climate change predictions for Werie catchment were analyzed using R software packages considering two emission scenarios of Representative Concentration Pathways known as RCP 4.5 and RCP 8.5.; Future climate change assessment in Werie catchment showed a significant increase of precipitation, minimum and maximum temperatures.; Application of a fully distributed hydrological WetSpa; Water and Energy Transfer between Soil, Plants, and Atmosphere, model in Werie catchment revealed that the model performs well to reproduce the observed streamflow values, hence can be used in similar climatic and hydrological conditions.; In the 21st century streamflow in Warie catchment in response to climate change is expected to experience an increase during the rainy summer (June to September) season and a decrease in the dry (October to May) season.;